SUMBER DAYA MANUSIA BERMARTABAT: DARI TEKNOKRATIK KE KARAKTER - I Wayan Gede Suacana (Public Inspiration : Jurnal Administrasi Publik, 2016)
Orthodoxy is the present state that we must prepare to face the challenges of the age symbolized by the new mysticism, the number "2020". Economic challenges most noticeable each country according to proponents of technocratic is to increase the added value potential (which can be donated by citizens respectively) to the global economy, by improving skills and their abilities and improving infrastructure facilities that can link the skills and expertise it with (the needs of ) the world market. The main component in this effort is to increase the ability to produce goods and services that are solid knowledge and information. In other words, the mastery of science and information technology (IT) is a necessity. Proponents of humanist-spiritualist want to equip it with the formation of good character in the process of human resource development. This strategy wants more "humanizing" human development by making themselves as the center (not industrial), with its main source of creativity and personal commitment (not capital).Key words: human resources, development, character